1979
DOI: 10.1584/jpestics.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the Residue in Soybean Plant after Treatment of Alloxydim-sodium

Abstract: The residue levels of apparent alloxydim-sodium (ADS), sodium salt of 2-(1allyloxyaminobutylidene)-5, 5-dimethyl-4-methoxycarbonylcyclohexane-l, 3-dione, in soybean seeds were studied using 14C-ADS compounds labeled at either C-7 or C-1, 5 position. The 14C-ADS was applied on the first trifoliate at the second trifoliate stage of the plant. One group of the treated plants was kept under the condition preventing from rainfall. Another group was showered artificially 3 or 7 days after treatment of 14C-ADS and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This byproduct was also detected in the photodegradation of alloxydim in environmental waters (Sandín-España et al 2013a;Sevilla-Morán et al 2008). Although several authors have reported the formation of the corresponding enamine of alloxydim (the tautomer of deallyoxylated alloxydim), as a result of biotic or abiotic reactions in sugar beet (Soeda et al 1979), soybean (Hashimoto et al 1979a(Hashimoto et al , 1979b, and sterilized soil (Ono et al 1984), to the best of our knowledge, the deallyoxylated alloxydim derivative has not been previously observed in any photodegradation study on plant leaves or soil surfaces.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…This byproduct was also detected in the photodegradation of alloxydim in environmental waters (Sandín-España et al 2013a;Sevilla-Morán et al 2008). Although several authors have reported the formation of the corresponding enamine of alloxydim (the tautomer of deallyoxylated alloxydim), as a result of biotic or abiotic reactions in sugar beet (Soeda et al 1979), soybean (Hashimoto et al 1979a(Hashimoto et al , 1979b, and sterilized soil (Ono et al 1984), to the best of our knowledge, the deallyoxylated alloxydim derivative has not been previously observed in any photodegradation study on plant leaves or soil surfaces.…”
Section: Resultsmentioning
confidence: 69%
“…Alloxydim absorbs light at wavelengths above 290 nm, so photochemical reactions caused by sunlight irradiation can be presumed. Little is known about its degradation on plant and soil surfaces (Hashimoto et al 1979a(Hashimoto et al , 1979bOno et al 1984;Soeda et al 1979;Veerasekaran and Catchpole 1982), and the majority of the photolysis studies of this compound have been performed in aqueous media (Iwataki and Hirono 1979;Sandín-España et al 2013a;Sevilla-Morán et al 2008). In previous studies performed by our group, we observed rapid degradation in river water with a half-life of 3.4 h under natural sunlight, and we identified a deallyoxylated compound and the Z isomer of alloxydim as the main by-products (Sandín-España et al 2013a).…”
mentioning
confidence: 81%
“…4). These three degradation products also appeared when alloxydim-sodium is applied in the leaves of plants (Hashimoto et al, 1979a;Koskinen et al, 1993).…”
Section: Chemical Degradationmentioning
confidence: 90%